A méretgazdaságosság vizsgálata Heves megye egyes mezőgazdasági kisvállalkozásainak példáján keresztül - Csernák, József; Ficzeréné Nagymihály, Kornélia; Zörög, Zoltán (Acta Carolus Robertus, 2011)
In our study, we aimed to examine the development of small agricultural enterprises. Our object was to survey current instead of the usual development successive study to analyze the current small business development position. In the courses of the work we have enquired the growth of the soil, and along with the relevant sectors, especially the profitability of the arable farming. During the survey, due to the exhaustive, we have dealt with the magnitude of the incurred costs, and their effects on small enterprises management
Keywords: agriculture; longitudinal panel-analysis; development successive